Conditional Cash Transfers As A Tool For SDG 1 Implementation (International Journal of Environmental Sciences, 2025)
This paper examines the role of Conditional Cash Transfers (CCTs) as strategic instruments for achieving Sustainable Development Goal 1 (SDG 1): No Poverty. Drawing from case studies in Latin America, Sub-Saharan Africa, and Southeast Asia, the study synthesizes empirical evidence on the impact of CCTs on income security, education, health outcomes, and multidimensional poverty reduction. Programs such as Bolsa Família (Brazil), Oportunidades (Mexico), 4Ps (Philippines), and LEAP (Ghana) illustrate that CCTs, when well-designed and effectively implemented, can simultaneously address immediate poverty and long-term human capital deficits. However, their success is conditioned by regional variations in administrative capacity, digital infrastructure, and political commitment.The findings underscore that CCTs align closely with SDG 1 targets, particularly 1.2 (multidimensional poverty reduction) and 1.3 (social protection systems), but also reveal persistent challenges including targeting errors, leakages, and conditionality enforcement gaps. The paper offers key policy recommendations, such as strengthening institutional integration, expanding graduation pathways, and enhancing supply-side service delivery. It concludes by identifying avenues for further research, particularly in urban settings, gender impacts, and tech-enabled delivery systems, highlighting the potential of CCTs to drive equitable and sustainable poverty reduction globally.